(untitled) (Sahel Journal of Life Sciences FUDMA, 2025)
This study investigated the impact of thermal and high-pressure processing (HPP) on the amino acid profile of Trichosanthes lobata, an underutilized plant with high nutritional potential. The objective was to evaluate how these food processing methods affect amino acid content, which directly influences the nutritional value of the plant. Samples of T. lobata were subjected to thermal treatment at 80°C, 90°C, and 100°C, and HPP at 250 MPa, 300 MPa, and 350 MPa. Amino acid concentrations were then analyzed and compared to unprocessed controls. Thermal processing resulted in a significant reduction (P ≤ 0.05) in amino acid content across all temperatures, with decrease in key amino acids such as leucine, lysine, isoleucine, and glutamic acid. Essential amino acids were especially vulnerable, indicating loss of nutritional quality even at moderate temperatures (80°C). In contrast, HPP at 250 MPa and 300 MPa preserved amino acid levels effectively, with no significant difference from the unprocessed samples (P > 0.05). However, at 350 MPa, there was amino acid degradation, suggesting a pressure threshold beyond which nutritional integrity is compromised. In conclusion, while thermal processing significantly diminishes the amino acid content of T. lobata moderate HPP (≤300 MPa) is a promising non-thermal alternative that preserves its protein quality. Despite its potential, limited studies have been conducted on the impact of thermal and high-pressure processing on Trichosanthes lobata. Given the importance of this plant as a functional food and medicinal ingredient, assessing how these processing techniques influence its amino acid profile is essential.